Apakah Apakah Mandatori CSR Dapat Meningkatkan Reputasi Perusahaan Dalam Industri Kontroversial? - Hasan, asmawati (Kodepena Indonesia, 2025)
Companies in controversial industries such as the cement industry typically face the risk of rejection from the surrounding community due to the environmental impact of their activities. This study examines the relationship between corporate social responsibility (CSR) obligations and the reduction of these risks. We develop and test hypotheses about CSR fit and CSR authenticity, and their relationship to perceived corporate reputation. CSR image is tested for its ability to act as an intervening variable in forming a positive relationship between CSR activities and corporate reputation. We use a sample from the community surrounding the PT Solusi Bangun Andalas cement factory in Aceh, Indonesia. Model estimation uses the Partial Least Square Structural Equation Model (PLS-SEM) method. We find that CSR image partially mediates the relationship between CSR fit and corporate reputation and fully mediates the relationship between CSR authenticity and corporate reputation. Important implications of these findings are: first, companies need to choose CSR activities that align with their core activities, despite their controversial nature, and implement them consistently. Second, their CSR activities must be related to the needs of the surrounding community, both in terms of the natural environment and social welfare.